Question 1 of 5Determine which Equation Matches the Graph
Select the Correct Answer Below: Correct! Not Correct!
A
$$\frac{x^2}{49}+\frac{y^2}{25}=1$$
B
$$\frac{x^2}{25}+\frac{y^2}{49}=1$$
C
$$\frac{x^2}{7}+\frac{y^2}{5}=1$$
D
$$\frac{x^2}{5}-\frac{y^2}{7}=1$$
E
$$\frac{x^2}{\sqrt{7}}-\frac{y^2}{\sqrt{5}}=1$$
Question 2 of 5Determine which Equation Matches the Graph
Select the Correct Answer Below: Correct! Not Correct!
A
$$\frac{x^2}{36}+\frac{y^2}{16}=1$$
B
$$\frac{x^2}{\sqrt{2}}-\frac{y^2}{\sqrt{6}}=1$$
C
$$\frac{x^2}{16}+\frac{y^2}{36}=1$$
D
$$\frac{x^2}{6}+\frac{y^2}{4}=1$$
E
$$\frac{x^2}{4}-\frac{y^2}{6}=1$$
Question 3 of 5Determine which Equation Matches the Graph
Select the Correct Answer Below: Correct! Not Correct!
A
$$\frac{(x-1)^2}{9}+\frac{(y-2)^2}{25}=1$$ $$\frac{(x-1)^2}{9}\hspace{.25em}+$$$$\frac{(y-2)^2}{25}=1$$
B
$$\frac{(x-2)^2}{5}+\frac{(y-1)^2}{3}=1$$ $$\frac{(x-2)^2}{5}\hspace{.25em}+$$$$\frac{(y-1)^2}{3}=1$$
C
$$\frac{(x-2)^2}{9}-\frac{(y-1)^2}{25}=1$$ $$\frac{(x-2)^2}{9}\hspace{.25em}-$$$$\frac{(y-1)^2}{25}=1$$
D
$$\frac{(x-2)^2}{25}+\frac{(y-1)^2}{9}=1$$ $$\frac{(x-2)^2}{25}\hspace{.25em}+$$$$\frac{(y-1)^2}{9}=1$$
E
$$\frac{(x-2)^2}{3\sqrt{5}}-\frac{(y-1)^2}{5\sqrt{3}}=1$$ $$\frac{(x-2)^2}{3\sqrt{5}}\hspace{.25em}-$$$$\frac{(y-1)^2}{5\sqrt{3}}=1$$
Question 4 of 5Determine which Equation Matches the Graph
Select the Correct Answer Below: Correct! Not Correct!
A
$$\frac{(x-1)^2}{16}+\frac{(y-2)^2}{4}=1$$ $$\frac{(x-1)^2}{16}\hspace{.25em}+$$$$\frac{(y-2)^2}{4}=1$$
B
$$\frac{(x-1)^2}{4}+\frac{(y-2)^2}{16}=1$$ $$\frac{(x-1)^2}{4}\hspace{.25em}+$$$$\frac{(y-2)^2}{16}=1$$
C
$$(x-1)^2-\frac{(y-2)^2}{\sqrt{2}}=4$$ $$(x-1)^2\hspace{.25em}-$$$$\frac{(y-2)^2}{\sqrt{2}}=4$$
D
$$\frac{(x-1)^2}{2}-\frac{(y-2)^2}{\sqrt{2}}=1$$ $$\frac{(x-1)^2}{2}\hspace{.25em}-$$$$\frac{(y-2)^2}{\sqrt{2}}=1$$
E
$$\frac{(x-2)^2}{16}+(y-1)^2=\sqrt{2}$$ $$\frac{(x-2)^2}{16}\hspace{.25em}+$$$$(y-1)^2=\sqrt{2}$$
Question 5 of 5Determine which Equation Matches the Graph
Select the Correct Answer Below: Correct! Not Correct!
A
$$\frac{(x-4)^2}{3}+\frac{(y+1)^2}{6}=\sqrt{3}$$ $$\frac{(x-4)^2}{3}\hspace{.25em}+$$$$\frac{(y+1)^2}{6}=\sqrt{3}$$
B
$$(x-4)^2+\frac{(y+1)^2}{36}=1$$ $$(x-4)^2\hspace{.25em}+$$$$\frac{(y+1)^2}{36}=1$$
C
$$\frac{(x+4)^2}{9}+\frac{(y-1)^2}{36}=1$$ $$\frac{(x+4)^2}{9}\hspace{.25em}+$$$$\frac{(y-1)^2}{36}=1$$
D
$$\frac{(x-4)^2}{\sqrt{3}}-\frac{(y+1)^2}{\sqrt{6}}=1$$ $$\frac{(x-4)^2}{\sqrt{3}}\hspace{.25em}-$$$$\frac{(y+1)^2}{\sqrt{6}}=1$$
E
$$\frac{(x-4)^2}{9}+\frac{(y+1)^2}{36}=1$$ $$\frac{(x-4)^2}{9}\hspace{.25em}+$$$$\frac{(y+1)^2}{36}=1$$

Great Job! You Passed!

Better Luck Next Time...

Restart Quiz ↻
Review Lesson ↻
Next Lesson »